A Literature Review of Dinamics Teacher Welfare in Indonesia - Purba, Della Priskila; Dita, Disa Martia; Vivaldy, Jeremy Akbar; Purba, Jon Felix; Simanjuntak, Septo; Bangun, Melly Br (Paedagogi: Jurnal Kajian Ilmu Pendidikan (e-journal), 2024)
The welfare of teachers plays an important role in improving the quality of education and professional performance. This article explores various dimensions of teacher well-being, including economic, psychological, and social aspects, and their impact on work motivation, competence, and teaching performance. The analysis also includes the influence of certification, workload, and role model teacher figures in building student readiness for a career as an educator. Self-efficacy is identified as a significant mediating variable in the relationship between teacher well-being and career readiness. This study uses a literature approach to understand the relationship between welfare policies, work motivation, and improving education quality. The results emphasize the importance of fair and inclusive welfare policies, accompanied by competency-based training programs, to support teachers as the spearhead of national education in the digital era. This article recommends strengthening synergy between the government, educational institutions, and the community to create a sustainable, quality education ecosystem.